Virtual Collaborative Learining as One of the Effective Strategies for Raising Cross-Cultural Awareness in Business English Classroom - Dolidze, Tamari; Mikeladze, Nino; Abesadze, Anna; Mansfield, Michael Jack (European Scientific Journal, ESJ, 2023)
Recently, Business English (BE) has become an integral part of teaching English due to its growing demand in the employment market and its power to facilitate cross-cultural communication and dialogue between speakers of all languages. Since BE serves as a Lingua Franca globally, a good mastery of the so-called Business English as Lingua Franca (BELF) is getting more and more attention among practitioners and researchers of Business English, who attempt to update their curriculum in accordance with cutting-edge developments for better occupational purposes. With this in mind, the presented paper will attempt to showcase the merits of Virtual Collaborative Learning (VCL) as one of the effective strategic tools for raising cross-cultural communication in the Business English classroom which indeed fosters the development of a culturally intelligent generation through support and guidance. The combined questionnaire was designed to study the experiences of BE learners–specifically, the experiences of former beneficiaries of Virtual Exchange in a shared Business English course between Grigol Robakidze University (Tbilisi and Batumi Campuses) and Azerbaijan Pedagogical University held during the Spring term of 2021. Since the representatives of different cultures were learning Business English via Virtual Collaborative Learning (VCL), they were automatically exposed to various intercultural contexts which aimed at raising their cross-cultural communication awareness through the use of BELF. The results of the questionnaire were applied to evaluate the effectiveness of Virtual Collaborative Learning to facilitate cross-cultural knowledge as a result of which VCL was/will be added as an integral part of the existing BE curriculum.